The following CDF, \begin{equation} F_{y}(x) = 1- \Big( \frac{ (1-\phi) x}{\phi (k-1)}+1\Big)^ {1-k} e^{- \frac{x}{\phi y}} \end{equation}

is approximated for $k \rightarrow \infty$ as follows \begin{equation} F_{y}(x) \approx 1- e^{- (\frac{1-\phi}{\phi}+ \frac{1}{\phi y})x} \end{equation}

I would like to obtain the approximation and tried to apply L'Hopital's rule (I am not sure whether it is the right approach) and I was not successful.

Can anyone guide me to find the approximation please? Thank you in advance.


Note that it suffices to approximate


by $e^{\frac{(\phi-1)x}{\phi}}$.

With the substitution $n=1-k$ and $r=(\phi-1)x/\phi$, this follows immediately from the fact that


You can prove this by L'Hospital applied to $\frac{\ln(1+rz^{-1})}{z^{-1}}$. Note that differentiation on top and bottom gives


which tends to $r$ as $z\to-\infty$.


We have that

$$\left( \frac{ (1-\phi) x}{\phi (k-1)}+1\right)^ {1-k}=e^{(1-k)\log\left( \frac{ (1-\phi) x}{\phi (k-1)}+1\right)}$$


$$(1-k)\log\left( \frac{ (1-\phi) x}{\phi (k-1)}+1\right)=-\frac{\log\left( \frac{ (1-\phi) x}{\phi (k-1)}+1\right)}{\frac 1{k-1}}=\\=-\frac{ (1-\phi) x}{\phi }\frac{\log\left( \frac{ (1-\phi) x}{\phi (k-1)}+1\right)}{\frac{ (1-\phi) x}{\phi (k-1)}}\to \frac{ (1-\phi) x}{\phi }$$

since, by standard limits, as $t \to 0$ we have $\frac{\log (1+t)}{t} \to 1$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.